Solar Energy Farm Site Selection Using GIS Multi-Criteria Decision Analysis Surrounding Kirkuk City - Nozad, Ammar Ayad; Shareef, Muntadher Aidi (Iraqi Journal of Science, 2025)
Kirkuk province needs a comprehensive and specialized strategy to address these difficulties and identify the most suitable solar energy solutions to reduce its ecological impact and improve its energy security and economic sustainability in future years. This study aims to present a framework for solar energy farm site selection working with Geographic Information System (GIS) and Multi-Criteria Decision Analysis (MCDA) techniques surrounding Kirkuk province, Iraq. Several spatial data sets were integrated in two steps to locate the best locations for solar energy farms. The first stage was to identify land availability with the elimination of constraints areas such as distance from major roads, distance from bodies of water, urban areas, distance from electric power transmission lines, and distance from industrial locations. The second stage was to choose the essential criteria, weigh them using an Analytical Hierarchy Process (AHP), and finally analyze the criteria using GIS to determine the best sites for solar energy farms. The available land results indicated their distribution in three regions with large areas, which are the north-east, north-west, and south-east, with a total area estimated at 40.182 km2, in addition to separate small areas of about 1.698 km2 in the rest regions of the study area. The highly suitable lands were dispersed throughout the northwest and north of the research region, covering a total area of 7.4304 km2, while medium suitable lands, indicated by the yellow color, are spread out in the southeast, with a total area estimated at 2.9376 km2. The low suitable lands cover some small areas south of the research area, shown in green, and cover an area of 1.8432 km2.